A comparison of the harmonic scalpel, coblation, bipolar, and cold knife tonsillectomy methods in adult patients - Subaşı, Buğra; Oğhan, Fatih; Taşlı, Hamdi; Karaman, Nesibe Esra; Akbal, Seçkin (Journal of Surgery and Medicine, 2021)
Background/Aim: Tonsillectomy is one of the widely performed surgical procedures by otolaryngologists. Today, many new surgical instruments are used in tonsil surgery to reduce postoperative morbidity. This study aimed to compare intraoperative blood loss, operating time, postoperative pain, and bleeding between harmonic scalpel tonsillectomy, coblation tonsillectomy, bipolar tonsillectomy, and cold dissection tonsillectomy in adult patients. Methods: This prospective cohort study population comprised 96 adult patients aged 18-60 years (mean age: 34.9 (10.7) years) who were operated on for chronic tonsillitis. The amount of bleeding and the operation time were calculated intraoperatively. Postoperative pain level was evaluated using a Visual Analogue Scale (VAS) at the sixth postoperative hour and on postoperative days 1, 2, 3, and 7. Results: In the harmonic scalpel group, the mean volume of intraoperative bleeding (2.7 (1.5) ml) and the mean operation time (8.8 (3.0) min) were significantly lower compared to the other groups (P<0.001, P<0.001 respectively). Secondary bleeding was detected in 10 patients but there was no significant difference in the post-tonsillectomy bleeding rates between the four groups (P=0.86). Pain scores at the sixth postoperative hour were similar and significantly lower in the harmonic scalpel, coblation, and bipolar groups compared with the cold dissection group (P<0.001). The postoperative pain scores were significantly higher in the harmonic scalpel group compared to the cold dissection group on postoperative days 3 and 7 (P=0.03, P=0.02 respectively). Conclusion: Less bleeding during surgery, shorter operation time, and less pain in the early postoperative period are the advantages of Harmonic scalpel tonsillectomy. Also, it does not increase the rate of secondary bleeding but its benefit for late period pain is lower compared to the cold knife method. The harmonic scalpel is a practical and reliable method in adult tonsil surgery.